Simultaneous Determination of Preservatives, Artificial Sweeteners, and Synthetic Dyes in Kimchi by Ultra-Performance Liquid Chromatography Electrospray Ionization Tandem Mass Spectrometry (UPLC-ESI-MS/MS). (2nd November 2019) - Lee, Hee Min; Yang, Ji-Su; Lee, Hae-Won; Hwang, In Min; Hwang, Ye Seul; You, Su-Yeon; Ha, Ji-Hyoung; Kim, Sung Hyun
Abstract: A simple and rapid method was developed for the simultaneous determination of five preservatives, six artificial sweeteners, and nine synthetic dyes in kimchi using ultra-performance liquid chromatography electrospray ionization tandem mass spectrometry (UPLC-ESI-MS/MS) with multiple reaction monitoring (MRM). The chromatographic separation was performed in 5.5 min using an Acquity UPLC BEH C18 column (100 mm × 2.1 mm, 1.7 µm) with a mobile phase composed of 0.002% trifluoroacetic acid and 10 mM aqueous ammonium acetate or 9:1 (v/v) methanol:acetonitrile. Linear calibration curves were obtained with correlation coefficients above 0.98. The limits of quantification ranged between 0.227 and 8.569 ng/mL, while the recovery values in kimchi samples were from 83.1 to 113.5%. Forty kimchi samples were analyzed for the food additives, with sweeteners detected in more than half of these samples. The most commonly detected sweetener was saccharin, and six of the kimchi samples contained a combination of sweeteners; dulcin, sucralose, acesulfame K, preservatives, and synthetic dyes were not detected. Based on these results, the developed method can be used for the rapid quality control of food additives in kimchi.